PENGARUH PENERAPAN STRATEGI PEMBELAJARAN AKTIF TIPE LEARNING STARTS WITH A QUESTION (LSQ) TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VII MTsN PALANGKI - Angriawan, Harry Meiwi; Haryono, Yulia; Fitri, Dewi Yuliana (Pendidikan Matematika, 2013)
The research is based on the less of students understanding of mathematical concepts and students ashame and did not want to ask question about the material they did not understand yet. The purpose of this research is to know whether the students understanding of mathematical concepts by using active learning types Learning Starts With a Question is better than the students mathematical concept that using conventional learning strategy. The kind of this research is experimental research, with random designtoward the subject of research. The population of this research is students of VII grade of MTsN Palangki in 2012-2013 academic year. The technique of sampling is doing by using random sampling, that was chosen as sample class is VII2 as experiment class and VII3 as control class. The instrument that is used in this research is post test of students understanding of mathematical concept. The test form that is used is essays with the reability of the test 0,89. The technique of data analisys is used test T by using MINITAB software. Based on the data analisys, it was gotten P-value is 0,00 it means smaller than Â = 0,05 , so that the hypothesis of this research is accepted so it can be concluded that the students understanding of mathematical concept by using active learning type Learning Starts With a Question is better than the students understanding of mathematical concept that is using conventional learning strategy of VII grade students of MTsN PalangkiÂ  in 2012-2013 academic year.